Digital Subtraction Angiography Findings in Aneurysmal Subarachnoid Haemorrhage: Experience of 30 Cases in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Digital subtraction angiography (DSA) is an important diagnostic tool for aneurysmal subarachnoid haemorrahage (SAH). Objectives: The purpose of the present study was to observe the findings of DSA in patients with SAH. Methodology: This cross-sectional study was performed in the Department of Neurology at Dhaka Medical College Hospital, Dhaka from December 2009 to November 2010 for a period of one (1) year. Patients at any age in both sexes who were admitted with SAH were included by purposive sampling technique. Demographic and clinical data were recorded in a semi-structured questionnaire. Angiography was performed after 4 weeks by DSA technique among all patients. Results: The mean age of the participants was 44.9±9.7 years (mean±SD). Male female ratio was 3:2. Hypertension, smoking, diabetes mellitus and family history of SAH were found in 14(46.6%) cases, 13(43.3%) cases, 3(10.0%) cases and 2(6.7%) cases patients respectively. All the study patients (100%) had headache and vomiting while 19(63.3%) cases had history of unconsciousness. Signs of meningeal irritation were present in 23(76.7%) patients. Anterior communicating artery was the most common site of aneurysm (36.7%) followed by middle cerebral (26.7%) and posterior communicating artery (23.3%). Majority of aneurysms were medium sized (46.7%), while 33.3% were small and 20.0% were large. Saccular aneurysm was found in 93.3% and aneurysms of narrow neck size in 86.7%. Conclusions: DSA has demonstrated that anterior communicating artery is the most common site of aneurysms in patients with SAH and is most often saccular with a narrow neck. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 51-54